Talking talent: Narratives of youth sports selection - Kilger, M. (2017)
In sports, there seems to be an eternal interest in discovering young talents and refining them into elite adult athletes. The dilemma of selecting talent, while at the same time ensuring every child´s right to participate, needs to be addressed and have consequences in social practice. This dissertation elucidates the discourse of selection and the process of selecting young sporting talents during final selection camps for youth national teams in football, hockey and floorball in Sweden. More specifically, the aim is to analyze how talent selection is organizationally legitimized, how "selectability" is produced in interaction and how specific narratives are used in success-stories. The empirical material includes research interviews, performance appraisal interviews (between district or national team coaches and the player) and field studies during ongoing final selection camp. Drawing on a discursive-narrative approach, the aim is to investigate how selection is discursively legitimized and, by using narrative analysis, how positioning in talk-in-interaction functions.